Social Change, Cohort Effects, and Dynamics of the Age–Crime Relationship: Age and Crime in South Korea from 1967 to 2011 - You, Myunghee (Journal of quantitative criminology, 2024)
ObjectiveThe goal of this study is to examine how the age-crime distribution in South Korea has shifted over time and the role of cohorts in driving this shift. This study highlights the impact of social change and historical events on cohort effects, potentially leading to shifts in the age-crime distribution..MethodsAge-Period-Cohort-Interaction (APC-I) models are estimated on age-specific-arrest statistics for offenses in South Korea from 1967 and 2011. The APC-I models take into account the interdependence of age, period, and cohort, thus permitting the identification of inter-and intra-cohort differences in crime over the life course.ResultsThe age-crime distribution in South Korea has changed over time to an older peak age of arrest. Korean baby boomers born between 1955 and 1963 have a higher risk of arrest earlier in life than other cohorts, perpetuating an overall increased risk over the life course.ConclusionChanges in socio-historical conditions differentiate crime trajectories across cohorts over the life course. Thus, this study suggests that social change and historical events impact the age-crime dynamics in South Korea.